2013
DOI: 10.1002/2013jg002415
|View full text |Cite
|
Sign up to set email alerts
|

Interannual drought length governs dissolved organic carbon dynamics in blackwater rivers of the western upper Suwannee River basin

Abstract: [1] The Little River (LR) in southern Georgia, U.S., has experienced lengthening droughts since monitoring began in 1972. We evaluated the impacts of drought on riverine carbon cycling using a 9 year data set of dissolved organic carbon (DOC) coupled with laboratory experiments in the LR, as well as long-term data sets in three additional rivers within the Suwannee River basin. Longer drought periods reduced downstream DOC export but also led to higher DOC concentrations in the following hydroperiod. Within a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 80 publications
1
18
0
Order By: Relevance
“…Mehring et al . [] reported similar results in the Suwanee River Basin and suggested that the increase in groundwater level (i.e., decrease in groundwater depth) could rapidly flush a highly labile DOC pool with a low density of aromatic moieties. Lambert et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mehring et al . [] reported similar results in the Suwanee River Basin and suggested that the increase in groundwater level (i.e., decrease in groundwater depth) could rapidly flush a highly labile DOC pool with a low density of aromatic moieties. Lambert et al .…”
Section: Discussionmentioning
confidence: 99%
“…The control of mean annual DOC concentrations by antecedent seasonal drought supports previous findings. Although performed in ecosystems as different as blackwater rivers in the Suwannee River basin, U.S. [ Mehring et al ., ] and Estonian rivers [ Parn and Mander , ], studies have shown that longer antecedent drought led to higher stream DOC concentrations. The present study demonstrated that in addition to the length of the dry season, the magnitude of the groundwater drawdown controlled mean annual DOC concentrations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5A). FPOM or dissolved organic matter (DOM) both contribute to ER, but concurrent measurements of DOM-associated respiration rates in the swamp averaged only 4% of leaflitter-associated O 2 demand on an areal (m −2 ) basis (Mehring et al 2013). Therefore, DOM respiration cannot fully explain the discrepancy between different estimates of O 2 demand.…”
Section: Discussionmentioning
confidence: 99%
“…CO 2 ) between terrestrial ecosystems and the atmosphere, there is also a horizontal pathway of A number of studies have shown that DOC riverine concentrations have been increasing over the past two to three decades, especially over Northern Europe and North America (Filella and Rodriguez-Murillo, 2014;Monteith et al, 2007;Evans et al, 2005;Grieve and Gilvear, 2008;Mehring et al, 2013;Tian et al, 2013;Oni et al, 2014;Sucker and Krause, 2010). Several hypotheses have been tendered as possible explanations for this DOC increase, including: decreasing atmospheric sulphur concentration; climate warming (with seasonal temperature increases); increasing precipitation with increasing annual (e.g.…”
Section: Dissolved Organic Carbon (Doc)mentioning
confidence: 99%